Competitive advantages observed in a cooperation network for selling sports goods - Vargas Bortolaso, Ingridi; Afonso Sellitto, Miguel (Revista Gestão da Produção Operações e Sistemas, 2009)
The objective of this paper was to identify and analyze competitive advantages that arose from networking activities by sports goods retailers that participate in a Cooperation Network in Rio Grande do Sul. The network is part of a program created by the State Secretary of Development and International Affairs. The network is comprised of twenty three stores associated with forty points-of-sale. The exploratory case study method was used. The main competitive advantages observed were: greater bargaining power; risk reduction; knowledge; shared marketing; and exchange of information. We identified and commented on the main information exchanged and shared by a set of firms sampled in the central part of the state. Keywords: cooperation network, networking competitiveness, networking information